Police IT ecosystem of Karnataka State Police - Maheshwari, Sunil Kumar, (SAGE business cases., 2019)
Sanjay Sahay, Additional Director General of Karnataka Police and the mastermind behind a fully operational IT ecosystem for Karnataka police reviewed the challenges and bottlenecks in the implementation of the system. He pondered upon the next steps in the direction of national implementation of the technology and his future career options. During the implementation of the technology, Sahay had encountered several problems including the inconsistency in the quality and capabilities of the vendors and thus the need for internal staffing and training. The training of the individuals posed a huge problem due to the huge training costs and thus a mode of reverse mentoring where the qualified constables served as experts in training the senior police officials evolved. Sahay noted that since certain crime related issues were state specific; there was a need to understand each of the issues before panning out to other states. Given his extensive experience and demanding style of management, Sahay could lead the development of the project despite major challenges. There was also a need for him to develop a successor to ensure the implementation of the project in other states.